Effect of Ultrasound Frequency and NaOH Concentration on Bioethanol Steam Palm Pretreatment Process - Sugiarto, Yusron; Mahfut, Luristya Nur; Rilek, Nada Mawarda; Atrinto, Ameiga Cautsarina Putri; Khotimah, Mujaroh (Fakultas Teknologi Pertanian Universitas Brawijaya, 2014)
Lignocellulosic has promising material for bioetanol production. One of the abundant material is the stem of a Palm. Stem of palm is a plantation of palm waste which has not been utilized optimally which is contain high cellulose. Every year Indonesia produce palm stem of 300.375 ktons. This waste can be develop to produce bioetanol. However, pretreatment processes conducted some researchers still do not optmimal. This is related to the particle size and the method of pretreatment of less than optimal so that led to an overhaul of the lignin insufficient, consequently increased levels of cellulose was not significant resulting in low yield by bioetanol. Therefore, the research was implemented using the process of pretreatment method ultasonifikasi in order to produce higher pulp with nano-sized particles that will yield ethanol derived stem of palm is higher. Research methods used in this research composed of two factors, namely the concentration of NaOH and frequency ultrasonic waves that are each composed last 3 levels. The analysis conducted was the influence of the concentration of NaOH and time ultrasonikasi to increased cellulose pretreatment process using PSA, SEM and a Cheason. For the analysis of the results, data, and best treatment using ANOVA. The best treatment was obtained by combination of 9 (2 M NaOH konsentasi and sonikasi frequency 60 Hz) and lignin (19.6%) cellulose (59.49%) and hemicellulose (11.8%).Keywords: Bioethanol, pretreatment, ultrasound, stem of Â palm